Moja podróż na Księżyc - Milewska, Monika (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article deals with the complicated fates of my radio drama Podróż na Księżyc [Journey to the Moon]. In it, I write about the inspiration I drew from the work on an article about the subject of death in early silent cinema. Researching the beginnings of world cinema, I could not have ignored the figure of Georges Meliès, the great Cinema Magician. I decided to devote a theatre play to him, in which I confronted his idealistic attitude, which led him to ruin, with that of the rational attitude of the father of cinema, Louis Lumière. I wrote the piece about the immortality that art. confers with the Teatr Atelier in Sopot in mind. The theatre, though, ceased operating and no other theatre was interested in the text. After several years, a coincidence led to me being invited to participate in an invited competition organised by ZAiKS and the radio station Dwójka. The drama Podróż na Księżyc took second place and was magnificently directed by Anna Wieczur-Bluszcz. The roles of these pioneers of cinema were filled by Jan Englert and Jerzy Radziwiłowicz. In 2015 a jury led by Elżbieta Pleszkun-Olejniczakowa awarded the drama the Grand Prix at the “Dwa Teatry” [Two Theatres] Festival in Sopot.